Prevalence of Human Papillomavirus Infection and Clinicodemographic Correlates among Women Attending a Tertiary-Care Hospital: A Cross-Sectional Study Using Cytological and Molecular Approaches. - Biswas, Tanusri; Chaudhury, Nabamita; Sengupta, Shreya; Nath, Arghya; Saha, Rituparna (International Journal of Endorsing Health Science Research, 2025)
Background: Cervical cancer remains a major cause of morbidity and mortality among women in low- and middle-income countries, driven primarily by persistent infection with high-risk HPV, especially types 16 and 18. Although cytology-based screening has reduced disease burden, its variable sensitivity highlights the need for complementary molecular methods. This study estimated HPV prevalence, characterized HPV-16/18 distribution, assessed associations with clinicodemographic and reproductive factors, and compared the diagnostic performance of Pap smear cytology and HPV qPCR in women attending a tertiary-care hospital. Methodology: A hospital-based cross-sectional study was conducted among 82 women referred for cervical evaluation. Cervical samples were subjected to conventional Pap smear cytology and PCR-based HPV testing. Broad-spectrum L1 PCR was used for HPV detection, followed by genotype-specific real-time PCR for HPV-16 and HPV-18. Clinicodemographic, reproductive, and clinical data were collected using a structured questionnaire. Associations with HPV infection were assessed using chi-square or Fisher’s exact tests, and diagnostic agreement between Pap smear and qPCR was evaluated using concordance measures. Results: HPV DNA was detected in 21 participants (25.6%). HPV positivity was significantly associated with diabetes mellitus, anaemia, higher parity (≥3), non-barrier or absent contraceptive use, and clinical symptoms including white vaginal discharge, menstrual irregularities, and abdominal pain. HPV infection was most frequent among women aged 41–50 years. Cytological abnormalities were identified in 22.0% of participants, with squamous cell carcinoma being the most common abnormal finding. Concordance analysis demonstrated substantial agreement between Pap smear cytology and HPV qPCR, highlighting their complementary diagnostic roles. Conclusion: HPV infection was common among women attending a tertiary-care referral clinic, with significant associations observed with metabolic comorbidities, reproductive factors, and selected clinical symptoms. The findings support the integration of cytological and molecular screening approaches to improve early detection and risk stratification, particularly in resource-constrained tertiary-care settings.